Potential for Floating Offshore Wind Energy in Japanese Waters - Henderson, A. R. (Institutional Knowledge at Singapore Management University, 2002)
The prospects for large scale commercialisation of sea-bed-mounted offshore windfarms are currently excellent, with the existing small-scale prototype windfarms currently being joined by the first large-scale parks in the shallow seas off the Danish, German, Swedish, Dutch, Belgian, British and Irish coasts. However other countries, including Japan, have much more limited regions of the shallow waters suitable for such developments and hence other concepts will also need to be utilised if offshore wind energy is also to become a major source of energy there.